The Influence Of Household Mother's Education Level On Purchase Decisions Through Online Store In The District Of Deli Serdang - Renny Lubis (Enrichment : Journal of Management, 2022)
The development of computer technology and the internet has had a major impact on people's lives. One of them is in buying and selling transactions. Buying and selling transactions are no longer limited by region and time, with the internet the scope of buying and selling can be wider. This study was conducted to determine the effect of the education level of housewives in Deli Serdang Regency in conducting transactions using online stores. The variable level of education is the dependent variable, while the selection of product types, brands, and reasons for using online stores is the independent variable. With this research, it is hoped that the relationship between the education level of housewives and the habit of using online stores can be found.